Synthesis and Characterisation of Conjugated Bis-Schiff Base and The Boron Difluoride Complexes as Dye-Sensitier for Dye Sensitised Solar Cell (DSSC) Application - Nursyafira Adzira, Halmi (Universiti Malaysia Sarawak, 2023)
Schiff base and their metal complexes have been widely used as photovoltaic materials due to their excellent pi-electron transfer properties along the molecule. In this study, a total of eleven conjugated symmetrical bis-Schiff base and its complexes with different pi-spacers have been synthesised and spectroscopically characterised in order to investigate their conversion efficiency in dye-sensitiser solar cell (DSSC). All compounds were substituted either without any substituent or with hydroxy (-OH) or methoxy (-OMe) as the electron donor and difluoro boron (BF2) as the electron acceptor. The symmetrical bis-Schiff base compounds (1a-4c) were synthesised by using condensation reaction and further proceeded to undergo complexation with boron trifluoride diethyl ether to produce boron difluoride complexes (1d and 2d). All compounds were adapted with some modifications from existing works but have not been tested as dye-sensitiser for DSSC. All the synthesised compounds were applied as dye-sensitiser in DSSC using titanium (IV) oxide (TiO2) coated on a fluoride doped tin oxide (FTO) glass as the working electrode and electric paint containing carbon black and graphite coated indium tin oxide (ITO) glass as the counter electrode. The power conversion efficiencies (PCE) of the eleven bis-Schiff base compounds were tested using a 100W LED light with multimeter and resistance set up. The efficiencies result was compared to N3 Dye as the benchmark standard. The results showed that the compound with aromatic ring bridge as the pi-spacer in para- position and methoxy (-OMe) substituent gave the highest efficiency at 0.0691% whereas compound with aromatic ring and difluoro boron (BF2) gave the lowest efficiency at 0.0012%. The presence of strong electron donor and extended pi-conjugation effect in the structure allows effective charge transfer along the molecule which affects the conversion efficiency of DSSC device.